1998
DOI: 10.1093/ajcp/109.1.69
|View full text |Cite
|
Sign up to set email alerts
|

Image Cytometric Measurement of Nuclear Proliferation Markers (MIB-1, PCNA) in Astrocytomas:Prognostic Significance

Abstract: I m a g e C y t o m e t r i c M e a s u r e m e n t o f N u c l e a r P r o l i f e r a t i o n M a r k e r s ( M I B -1 , P C N A ) i n A s t r o c y t o m a s1 " 3 For astrocytomas, the proliferative capability of the neoplasm becomes increasingly important because of the confines of the skull and the rapidity of the onset of symptoms as the tumor enlarges. Additional insight into the behavior of astrocytomas has been gained by evaluating the proliferative activity for individual neoplasms. This approach is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
17
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 14 publications
3
17
2
Order By: Relevance
“…This is not in keeping with earlier studies which have shown that grade reliably predicts survival in astrocytoma patients [15,16]. The lack of significant difference in survival in the present study could be due to the short follow up available for most of the patients and the low numbers in Grade I and Grade III tumors.…”
Section: Pcna and Recurrencecontrasting
confidence: 95%
See 2 more Smart Citations
“…This is not in keeping with earlier studies which have shown that grade reliably predicts survival in astrocytoma patients [15,16]. The lack of significant difference in survival in the present study could be due to the short follow up available for most of the patients and the low numbers in Grade I and Grade III tumors.…”
Section: Pcna and Recurrencecontrasting
confidence: 95%
“…This relation has been seen in other series with large number of cases snd utilising other proliferation markers as well [7,16,20,22,23]. The range of PCNA LI is variable, from 0.00-30.96% in some studies [20,23] to 0.1-95% in others [7,16,22]. Our range of 0.4-72% was comparable with the second group.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…66,67 Earlier studies from our department established the role of Ki-67 quantitation in glial neoplasms. 68,69 Recently, using multimodal, multiscale approaches and machine-based classification, researchers have devised ways to mine scanned histologic data on glioblastoma in The Cancer Genome Atlas Project and other sources; the resulting quantitative morphometric analysis findings have been further integrated with molecular data to provide in silico cancer research [70][71][72][73][74][75][76][77][78][79][80] and with radiologic data to provide clinicopathoradiologic correlation. 81 Insights from this work also include findings on the importance of tumor-infiltrating lymphocytes in glioblastoma, 72 and in silico approaches from these studies have uncovered novel findings regarding the regulation of asymmetric cell division in glioblastoma by such mediators as the human Brat ortholog TRIM3.…”
Section: Neuropathologymentioning
confidence: 99%
“…It has been suggested that the MI of gliomas can have a predictive value in their own prognosis 6,24 . Ehrmann et al 25 demonstrated a relationship between cell proliferation (as measured by the PCNA protein expression) and the prognosis of 42 astrocytic tumors.…”
Section: Discussionmentioning
confidence: 99%